Multilocular subcutaneous bacillary angiomatosis as a primary manifestation of AIDS - Theresa M. Duckwitz; Amir S. Yazdi; David Kluwig (Wiley, 2024)
Abstract A 34‐year‐old male patient presented with a clinical picture of multilocular subcutaneous skin nodules in addition to marked lymphadenopathy and general physical deterioration. A comprehensive diagnostic workup including serology, skin biopsy and imaging studies led to the initial diagnosis of human immunodeficiency virus (HIV) infection in AIDS stage with rare multilocular subcutaneous bacillary angiomatosis (BA) caused by Bartonella henselae. BA describes a process of neovascularisation of the skin or of internal organs (particularly the liver and spleen) and was first described in HIV‐positive patients by Stoler et al. in 1983. Both cutaneous and systemic symptoms are variable. There is no standardized treatment. The patient was started on antibiotic therapy with doxycycline, which was subsequently augmented with rifampicin. As the patient's general condition deteriorated and lymphocytopenia aggravated, he was transferred to an internal medicine ward for further treatment and subsequently commenced on antiretroviral therapy. This case corroborates numerous aspects of the cases described in the literature yet differs from them in that subcutaneous lesions are uncommon, particularly when infected with Bartonella henselae, illustrating the clinical spectrum of BA. Furthermore, it emphasises the significance of prompt and thorough diagnosis encompassing HIV serology in instances of skin lesions, accompanied by systemic signs and evidence of immunosuppression.